Analisis Faktor-Faktor Konflik serta Pengaruhnya terhadap Produktividas Pekerja pada Perusahaan Tekstil PMDN dan PMA di Jawa Barat - Sutisna, Deden (Business and Management Review, 2011)
In West Java the textile companies strategically play a very important role in regional development. Among others this sector  can absorb great amount of  manpower to support the national textile exports. In relation to the conflicts, it is impossible to separate it from the conflict because this sector is quite dependent upon manpower, raw materials of imports and a very high market quota. The objective of this research is to know ( (1) its great influence of the factors of organizational composition, communication, personal characteristics, interpersonal, the differences of partial and simultaneous issues upon functional an disfunctional conflicts, (2) its magnitude influence of the  functional and disfunctional conflicts partially and simultaneously upon the productivity of workers. This research was carried out in West Java, by applying unit analysis of PMDN (Domestic Capital Invesment) and PMA (Foreign Capital Investment) textile companies, including the elements of the management and workers. The research method applied is by measuring 100 samples out of population of 250 companies. The technique of obtaining samples was by simple random sampling and the data analysis using structural equation modelling (SEM). The results of the research revealed that (1) partially and simultaneously, there is the influence of the factors of organizations composition, communications, personal characteristics, interpersonal, difference and issues upon functional and disfunctional conflicts, (2) functional and disfunctional conflicts, partially as well as simultaneously, have great influence upon the productivity of workers. From the six factors of resources mentioned above, the personal characteristic possessed by workers individually, have greater influence upon the two conflict  compared with other factors. On the other side, the productivity of workers  is more influenced by disfunctional conflicts rather than functional one.   Keywords : Organizational composition, communication, personal characteristics, interpersonal,  functional and disfunctional conflicts